AN EMPIRICAL STUDY ON THE IMPACT OF SUSTAINABILITY REPORTING ON FINANCIAL PERFORMANCE: INVESTMENT EFFICIENCY AS A MODERATING VARIABLE IN THE CONTEXT OF FINANCIAL COMPANIES - Sia, Jocelyn Larisa Jono; Margaretha Tarigan, Thia (Universitas Multimedia Nusantara, 2025)
Abstract - This study attempts to examine how sustainability reporting affects financial performance in financial firms using investment efficiency as a moderating variable listed on the Indonesia Stock Exchange (IDX). This study's sample consisted of 98 financial firms that were listed on the IDX, had complete annual reports from 2019 to 2023, and did not cease operations during that time. The data analyzed were expressed in Rupiah (IDR). The results of the study showed that Sustainability Reporting had an effect on Financial Performance, this shows that the commitment to sustainability stated in Sustainability Reporting can improve the company's Financial Performance. Furthermore, it has been demonstrated that investment efficiency moderates the relationship between financial performance and sustainability reporting. This means that businesses with effective investment management are better able to translate sustainability practices into profitable outcomes. This demonstrates that effective investment management is crucial for bolstering the beneficial impact of sustainability reporting on financial performance, boosting the company's appeal to investors, and promoting peak performance. Keywords: Sustainability Reporting; Financial Performance; Investment Efficiency.